Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.bcp.2010.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory actions of a taurine analogue, ethane β-sultam, in phagocytic cells, in vivo and in vitro

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A c c e p t e d M a n u s c r i p t 1 2 3 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…In our recent studies [25], we clearly showed that the anti-inflammatory property of taurine was mediated via stabilisation of IkaBa, thus preventing activation of NFkappaB. Although taurine can be synthesised intracellularly from cysteine and methionine, the diet is the main source for human nutrition.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In our recent studies [25], we clearly showed that the anti-inflammatory property of taurine was mediated via stabilisation of IkaBa, thus preventing activation of NFkappaB. Although taurine can be synthesised intracellularly from cysteine and methionine, the diet is the main source for human nutrition.…”
Section: Introductionmentioning
confidence: 98%
“…Although taurine can be synthesised intracellularly from cysteine and methionine, the diet is the main source for human nutrition. Taurine uptake from the plasma is tightly controlled by the taurine transporter, TauT, such that supplementation with taurine will only transiently increase taurine levels within the liver and to a lesser extent in the brain [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The field is dominated by the β-lactams (1) [ Figure 1] due to the importance that they have acquired as anti-infective agents. [1][2][3] The corresponding β-sultams (2) are also known and have attracted attention as taurine precursors, 4,5 β-lactamase inhibitors, 6 D,D-peptidase inhibitors, 7 human neutrophil elastase inhibitors, [8][9][10] azoreductase inhibitors, 11 anti-inflammatory agents, 12 potential treatments for alcohol dependency, 13 SPase I inhibitors 14 and ClpP protease inhibitors, 15 and have attracted other mechanistic 16,17 and synthetic efforts. [18][19][20] β-Sultam chemistry been a focus of our research for some time.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] β-Sultam chemistry been a focus of our research for some time. [6][7][8][9][10]12,13,17 …”
Section: Introductionmentioning
confidence: 99%